COMPARATIVE EFFECTIVENESS STUDY OF COMBINED ANTIHYPERTENSIVES FOR NIGERIAN PATIENTS - UKWE, CHINWE VICTORIA; ADIBE, MAXWELL OGOCHUKWU; CE, OKAFOR; C, ANOSIKE; A, ISAH; SO, IKE; BC, ANISIUBA; GC, NWURUKU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to compare the clinical and economic effectiveness of four combination antihypertensives recommended for Nigerians. Methods: An open, randomized, controlled, and longitudinal double-blind trial of four groups of antihypertensives combinations: Telmisartan/ chlorthalidone/amlodipine (TCA), TC, CA, and TA was conducted among hypertensive patients. The participants were recruited from three hospitals in Enugu, and randomly assigned to the study groups. The primary outcome for this study was blood pressure (BP) control, based on Joint National Committee-8 and cost per BP control. The secondary outcomes were cost per quality adjusted life years (QALY) and patients’ self-reported health status. Descriptive and inferential statistics were used for statistical analysis. Results: Of the 110 patients enrolled in the study, more than half were women (55.5%). The mean age of patients was 54.93±12.38. The enrollees had hypertension for over 9 years (9.17±8.40). About 77% of the patients completed the study in all the groups except for TA (66.7%). There was no difference in BP in all the groups at baseline and at end-of-study (p>0.050). However, the probability of BP control was highest in TCA group (0.37±0.01), followed by TC group (0.23±0.02). The TA group showed the most favorable cost per QALY, then CA, TC, and TCA in that order. The group with the most favorable cost per BP control was TCA (70.92±0.04), then TA (94.16±0.05). Conclusion: The triple combination therapy of TCA had the best cost per BP control in the management of hypertensive patients. It demonstrated the highest probability of BP control.